Tumor microenvironment in head and neck squamous cell carcinoma: Functions and regulatory mechanisms. (1st June 2021) - Wang, Ganping; Zhang, Ming; Cheng, Maosheng; Wang, Xiaochen; Li, Kang; Chen, Jianwen; Chen, Zhi; Chen, Shuang; Chen, Jie; Xiong, Gan; Xu, Xiuyun; Wang, Cheng; et al.
Abstract: The tumor microenvironment has been recently reported to play a pivotal role in sustaining tumor cells survival and protecting them from immunotherapy and chemotherapy-induced death. It remains largely unknown how the specific signaling pathway exerts the tumor microenvironment in head and neck squamous cell carcinoma though previous studies have elucidated the regulatory mechanisms involve in tumor immune microenvironment, stromal cells, tumor angiogenesis and cancer stem cell. These components are responsible for tumor progression as well as anti-cancer therapy resistance, leading to rapid tumor growth and treatment failure. In this review, we focus on discussing the interaction between tumor cells and the surrounding components for better understanding of anti-cancer treatment ineffectiveness and its underlying molecular mechanisms. Highlights: The tumor microenvironment has been recently reported to play a pivotal role in sustaining tumor cells survival, promoting tumor recurrence and anti-cancer treatment resistance. It remains largely unknown the molecular mechanism of the tumor microenvironment in head and neck squamous cell carcinoma (HNSCC) though previous studies have proved some factors involve in tumor immune microenvironment, such as stromal cells, tumor angiogenesis and cancer stem cell. Here, we discuss the recent research about the interaction between tumor cells and the surrounding components for better understanding of regulatory network driven by the tumor microenvironment in HNSCC.